A INFLUÊNCIA DA COMUNICAÇÃO ORGANIZACIONAL PARA A VIABILIZAÇÃO DA LOGÍSTICA REVERSA: um recorte do setor de pilhas e baterias (Comunicação & Inovação, 2024)
Reverse Logistics (RL) bring a innovative contribution by enabling the return remains to the production process, but is incipient in Brazil. This study evaluated whether demographic variables and variables associated with organizational communication influence consumer adherence to the practice of RL for batteries. Two stages of research were undertaken: a documental analysis and a survey. The results showed that "Stimulation through communication" was a significant predictor of adherence to RL, increasing the chance of RL for batteries by 21.4%.
Keywords: Organizational communication; Reverse logistic; Batteries